Obesity Increases Gene Expression of Markers Associated With Immunosenescence in Obese Middle-Aged Individuals - Brunelli, Diego T.; Boldrini, Vinicius O.; Bonfante, Ivan L. P.; Duft, Renata G.; Mateus, Keryma; Costa, Leonardo; Chacon-Mikahil, Mara P. T.; Teixeira, Ana M.; Farias, Alessandro S.; Cavaglieri, Cláudia R. (Frontiers in Immunology, 2022)
Recently, it has been argued that obesity leads to a chronic pro-inflammatory state that can accelerate immunosenescence, predisposing to the early acquisition of an immune risk profile and health problems related to immunity in adulthood. In this sense, the present study aimed to verify, in circulating leukocytes, the gene expression of markers related to early immunosenescence associated with obesity and its possible relationships with the physical fitness in obese adults with type 2 diabetes or without associated comorbidities. The sample consisted of middle-aged obese individuals (body mass index (BMI) between 30-35 kg / m²) with type 2 diabetes mellitus (OBD; n = 17) or without associated comorbidity (OB; n = 18), and a control group of eutrophic healthy individuals (BMI: 20 - 25 kg / m²) of same ages (E; n = 18). All groups (OBD, OB and E) performed the functional analyses [muscle strength (1RM) and cardiorespiratory fitness (VO2max)], anthropometry, body composition (Air Displacement Plethysmograph), blood collections for biochemical (anti-CMV) and molecular (gene expression of leptin, IL-2, IL-4, IL-6, IL-10, TNF-α, PD-1, P16ink4a, CCR7, CD28 and CD27) analyses of markers related to immunosenescence. Increased gene expression of leptin, IL-2, IL-4, IL-10, TNF-α, PD-1, P16ink4a, CCR7 and CD27 was found for the OBD and OB groups compared to the E group. Moreover, VO2max for the OBD and OB groups was significantly lower compared to E. In conclusion, obesity, regardless of associated disease, induces increased gene expression of markers associated with inflammation and immunosenescence in circulating leukocytes in obese middle-aged individuals compared to a eutrophic group of the same age. Additionally, increased adipose tissue and markers of chronic inflammation and immunosenescence were associated to impairments in the cardiorespiratory capacity of obese middle-aged individuals.